Biomass Valorization to Chemicals over Cobalt Nanoparticles on SBA-15 - Wega Trisunaryanti; Triyono Triyono; Elizabeth Selia Nandini; Endah Suarsih (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
A series of heterogeneous catalysts based on cobalt supported on SBA-15 were prepared through wet impregnation and co-impregnation assisted by ethylene glycol (EG) methods. The cobalt oxide catalysts generated after the drying and calcination process were denoted as CoO/SBA-15w and CoO/SBA-15c for a wet- and co-impregnation method, respectively. Subsequent to the reduction process, the reduced cobalt catalysts were obtained and denoted as Co/SBA-15w and Co/SBA-15c. The TEM images revealed the catalysts prepared through these methods show very clear distinctions that the catalyst prepared by wet impregnation shows large aggregates of cobalt particles on the external surface of SBA-15 due to their inability to enter the channels. The catalysts were evaluated on the hydrocracking of pyrolyzed -cellulose as a biomass model. The results showed that the reduced cobalt-based catalysts are having higher conversion value and selectivity towards the 2-furancarboxaldehyde reached ca. 20%. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).